Beyond the initial export boost: The erosion of trade agreement benefits - Eyal Ronen (Central European Economic Journal (CEEJ), 2024)
Preferential trade agreements (PTAs) are widely acclaimed for their potential to mitigate market imperfections and expand export opportunities. However, in changing economic circumstances, these beneficial effects may only endure for a while and often gradually fade, affecting industries unevenly. This study delves into this overlooked phenomenon by exploring Poland's export performance in the Western Balkan (WB) region, where the implementation of Stabilization and Association Agreements (SAAs) has evidently generated export growth, primarily driven by tariff reductions, though these gains were manifested disproportionally across sectors. Employing survival analysis, the study validates the positive influence of SAAs on Polish export competitiveness within the WBs while uncovering its temporal erosion and sectoral discrepancies. On average, a 51% and 84% decline in Polish export competitiveness to WBs is observed after 5 and 10 years, respectively. Moreover, a unique dataset on non-tariff measures (NTMs) is employed to identify specific sectors encountering significant NTMs contributing to the reported diverse export patterns. These insights highlight the need for policies that acknowledge the diminishing benefits of trade agreements and mitigate the trade imbalances caused by NTMs.
Keywords: C41; F13; 330; Export competitiveness; Non-Tariff Measures; Survival analysis; Trade agreements